2021
DOI: 10.1021/acs.biomac.1c00435
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Far-Red Light with Plant Antenna Complexes Incorporating Chlorophyll d

Abstract: Increasing the absorption cross section of plants by introducing far-red absorbing chlorophylls (Chls) has been proposed as a strategy to boost crop yields. To make this strategy effective, these Chls should bind to the photosynthetic complexes without altering their functional architecture. To investigate if plant-specific antenna complexes can provide the protein scaffold to accommodate these Chls, we have reconstituted the main light-harvesting complex (LHC) of plants LHCII in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…These red‐shifted chlorophylls d and f with absorption maxima at 740 and 760 nm, respectively, have been discovered in certain cyanobacterial species (Li and Chen, 2015). The novel chlorophyll d is predicted to be able to bind to LHC proteins, expanding the range of light absorption of chlorophyll a beyond 700 nm into the far‐red region, which is often found in the lower canopy of plants and could therefore enhance light harvesting and boost crop yields (Elias et al, 2021). Cyanobacterial OCP, on the other hand, absorbs wavelengths in the blue–green region and is attached to the light‐harvesting antennae (phycobilisomes), where it is responsible for photoprotective dissipation of excess light energy as heat (NPQ) and scavenging of ROS (Muzzopappa and Kirilovsky, 2020).…”
Section: Improving Crop Yields Through Optimization Of Photosynthetic...mentioning
confidence: 99%
“…These red‐shifted chlorophylls d and f with absorption maxima at 740 and 760 nm, respectively, have been discovered in certain cyanobacterial species (Li and Chen, 2015). The novel chlorophyll d is predicted to be able to bind to LHC proteins, expanding the range of light absorption of chlorophyll a beyond 700 nm into the far‐red region, which is often found in the lower canopy of plants and could therefore enhance light harvesting and boost crop yields (Elias et al, 2021). Cyanobacterial OCP, on the other hand, absorbs wavelengths in the blue–green region and is attached to the light‐harvesting antennae (phycobilisomes), where it is responsible for photoprotective dissipation of excess light energy as heat (NPQ) and scavenging of ROS (Muzzopappa and Kirilovsky, 2020).…”
Section: Improving Crop Yields Through Optimization Of Photosynthetic...mentioning
confidence: 99%
“…This ambitious strategy originated with the discovery of red‐shifted cyanobacterial Chl d (Miyashita et al ., 1996) and f types (Nürnberg et al ., 2018), the latter being characterized in terms of its biosynthetic pathway (Trinugroho et al ., 2020). The idea of expressing red‐shifted Chls in the understory leaves of the canopy as a way of increasing light‐harvesting capacity has recently attracted attention based on in vitro evidence that plant Lhc can bind these chromophores (Elias et al ., 2021) in a stable manner and maintain functional excitation energy transfer. However, this approach is complicated by at least three major issues: the enzyme(s) responsible for the synthesis of Chl d has yet to be elucidated; the biosynthesis of the heterologous pigment(s) must be implemented in the plant; and the ability to absorb low‐energy far‐red photons could slow down energy trapping, especially in PSII RCs, ultimately reducing LUE (Mascoli et al ., 2020).…”
Section: A Synthetic Antenna: Myth or Reality?mentioning
confidence: 99%
“…Such modularity may be more difficult to generate with alternative approaches employing covalent crosslinking of a dye directly to the LH protein complex [21][22][23][24]61]. Other studies have shown that non-native chromophores may be non-covalently incorporated into the natural pigment binding sites of LH complexes [62][63][64] by reconstituting the apoprotein with the desired free pigments. However, the new pigments must have suitable chemistry for favourable interactions with binding site residues, making precise control of which pigments can bind challenging [32].…”
Section: Benefits and Drawbacks: Protein-dye Self-assembly Versus Cov...mentioning
confidence: 99%